The Safavid State until the Battle of Chaldiran (1501-1514 AD) - قريش, منى; ربيع عثمان,; ايمن صلاط, (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
Political diversity in Iran was a scene from the history in which the Safavid dynasty lived, as Iran witnessed during this period a religious conflict that led to the division of its regions and the dispersion of its cities under the rule of a number of governments and families. It also witnessed a new wave of foreign invasion represented by the successive wars of Tamerlane, which ultimately resulted in Iran becoming part of a vast empire. As for the Safavid relations with the neighboring countries, there were no border disputes between the Mamluks and the Safavids, unlike the situation between the Mamluks and the Ottomans, as the Safavid-Ottoman conflict was an integrated conflict and the factors of geography, politics and economics combined to create it. However, its sectarian aspect was the most prominent and famous aspect, as Sultan Selim I prepared to fight the Safavids, whom he had intense hatred for, and war broke out between the two parties and culminated in the Battle of Chaldiran in 1514, which ended with the defeat of the Safavids, beginning a new phase in the history of the region at that time. The Safavid-Ottoman conflict was supported and fueled by the European countries, which exploited it to their advantage, and considered it one of the mechanisms to weaken the two states, as they sought through it to curb the continuous expansion of the Ottoman state on its lands and in the Arabian Gulf. This conflict resulted in the depletion of the power of the Safavids and Ottomans, both in terms of manpower and material, and the dispersion of the efforts of the Ottoman state between the eastern and western fronts, and the weakening of its ability to withstand in the middle of Europe.